A255 FULL-THICKNESS ENDOSCOPIC COLONIC RESECTION USING AN OVER-THE-SCOPE CLIP: A CASE REPORT. (1st March 2018) - Shahidi, N C; Moosavi, S; Xiong, W; Lam, E
Abstract: Background: Endoscopic mucosal resection (EMR) and endoscopic submucosal dissection (ESD) are established methods for removing colonic polyps. However, both have their limitations, specifically in the setting of recurrence with scarring and fibrosis increasing the technical difficulty and the potential for procedure-related adverse events. Aims: To describe the first Canadian experience of endoscopic full-thickness resection performed with an over-the-scope clip. Methods: Case Report. Results: A previously healthy average-risk 80-year-old female underwent colonoscopy (CSPY) for a positive fecal immunochemical test (871 ng/ml) which identified a 20mm sessile ascending colon polyp. On staged CSPY, the polyp was removed by EMR and the resection site tattooed. Pathology showed tubular adenoma with focal high-grade dysplasia. After 6 months, interval CSPY was performed which identified recurrence of a 10mm sessile polyp at the previous resection site. During EMR a "non-lifting" sign was identified with methylene blue injection. Therefore, biopsies of the resection site were taken. Pathology of the EMR specimen showed tubular adenoma however biopsies of the resection site showed fragments of tubular adenoma with high-grade dysplasia. In follow-up, the risks and benefits of surgery versus endoscopic resection were discussed and the patient consented for endoscopic full-thickness resection. The patient was positioned in left lateral decubitus and received conscious sedation (total: midazolam 3mg intravenous; fentanyl 50 mcg intravenous). Using a pediatric colonoscope, equipped with an over-the-scope clip device, the previous resection scar was identified. Cautiously, the scar and surrounding bowel were brought into the cap with gentle suction; After which the over-the-scope clip was deployed. Using a hexagonal snare, the bowel entrapped by the over-the-scope clip was then resected in a single specimen. No subsequent endoscopic intervention was required and the endoscope was withdrawn with no immediate peri-procedural complications. On pathology, a single polypoid fragment showed residual tubular adenoma with no high-grade dysplasia and clear margins. Deep aspects of the biopsy contained muscularis propia highlighting full-thickness resection. Conclusions: This is the first Canadian experience of endoscopic full-thickness resection. It highlights not only the safety of the procedure, but also the feasibility with conscious sedation. Funding Agencies: None